2016
DOI: 10.1186/s12940-016-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Short-term markers of DNA damage among roofers who work with hot asphalt

Abstract: BackgroundRoofers are at increased risk for various malignancies and their occupational exposures to polycyclic aromatic hydrocarbons (PAHs) have been considered as important risk factors. The overall goal of this project was to investigate the usefulness of phosphorylated histone H2AX (γH2AX) as a short-term biomarker of DNA damage among roofers.MethodsBlood, urine, and dermal wipe samples were collected from 20 roofers who work with hot asphalt before and after 6 h of work on Monday and Thursday of the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…[ 172 , 173 ]). LC-MS/MS is the main methodology for the majority of these matrices, emphasizing the strength of this approach, although ELISA has been used for serum [ 125 , 174 , 175 ], saliva [ [176] , [177] , [178] , [179] ], sputum [ 180 ], follicular fluid [ 169 , 170 ], and urine [ [181] , [182] , [183] , [184] ] (for others, see the ELISA section below).…”
Section: Measurement Of Oxidised Nucleic Acid Products In Extracellular Biological Matricesmentioning
confidence: 99%
“…[ 172 , 173 ]). LC-MS/MS is the main methodology for the majority of these matrices, emphasizing the strength of this approach, although ELISA has been used for serum [ 125 , 174 , 175 ], saliva [ [176] , [177] , [178] , [179] ], sputum [ 180 ], follicular fluid [ 169 , 170 ], and urine [ [181] , [182] , [183] , [184] ] (for others, see the ELISA section below).…”
Section: Measurement Of Oxidised Nucleic Acid Products In Extracellular Biological Matricesmentioning
confidence: 99%
“…12 As an internationally recognized biomarker of DNA oxidative damage, 8-OHdG is stabilized in the body; it is not affected by the diet or cellular renewal and it can be induced by various xenobiotics. 13-15 Several studies have also suggested that 8-OHdG is linked to many kinds of diseases, from tumors, cardiovascular disease to diabetes. 16-18 However, to the best of our knowledge, few previous studies have evaluated the impact of IR on 8-OHdG levels.…”
Section: Introductionmentioning
confidence: 99%
“…B[ a ]P is a known group 1 carcinogen according to the IARC [9,10], while other genotoxic HMW PAHs are primarily classified as group 2B, “possibly carcinogenic to humans”. However, low molecular weight (LMW; 2–4 rings) PAHs are more abundant than HMW PAHs, such as B[ a ]P, in primary and SHS smoke from cigarettes and marijuana (e.g., fluoranthene), in air pollution as components of particulate matter, as well as potential occupational hazards for those workers in industries such as coal, coke, and steel [1,2,3,9,11,12,13,14,15,16,17]. For example, in SHS, the level of 2–4 ring LMW PAHs is ~20 times that of the HMW PAHs [2] and in the Kentucky 1R1 reference cigarette smoke condensates, the methylated anthracenes (LMW PAHs) are 62 times higher than B[ a ]P and benzo( e )pyrene [11].…”
Section: Introductionmentioning
confidence: 99%